Indicadores para el estudio de las publicaciones oficiales en españa - Ayuso García, M.ª Dolores; Martínez Navarro, Victoria (Revista General de Información y Documentación, 2002)
The most important indicators offered by official statistics for the study of the editiorial activity of the public authorities in Spain are introduced in this article which also tries to elucidate the reasons why a substantial part of the official publications in Spain is to be found in the field of Grey Literature. We delimit and introduce the statistical sources with which we have worked for the definition of indicators for the study of official publications in Spain. From these indicators the present day nature of the institutional edition is established. Finally, analysis is made of the mechanisms of bibliographic control, which are operative at the present time over official publications with an informative purpose, taking into account that a large number of these belong to Grey Literature. Conclusions are drawn after the relevant statistical analysis. Among these we should point out, on the basis of data supplied by statistics on official edition in Spain, always according to data faciliatated by de ISBN Spanish Agency and Legal Deposit, the essential role of the regional bibliographies in the bibliographic control of official publications.
Keywords: Official publications; Grey Literature; Non conventional literature; Bibliographic control; Legal deposit; ISBN Spanish Agency; Public edition; Statistical studies; Spain